Fruit handling and ergonomic practices in fruit industry / Muhammad Imran Roslan, Azeerul Zharif Sarip and Muhammad Faris Mohd Nor - Roslan, Muhammad Imran; Sarip, Azeerul Zharif; Mohd Nor, Muhammad Faris (Faculty of Plantation and Agrotechnology, 2023)
Malaysia is a major producer of tropical fruits such as durian, mango, pineapple, banana, and papaya. The fruit industry is important to Malaysia's economy, with many farmers and businesses involved in production and export. Malaysia produces high-quality fruit that is in demand globally. Proper fruit harvesting and handling techniques are important for preserving the quality of the fruit. Back pain is common among agricultural workers due to the physical demands of the work. Factors that can contribute to back pain include heavy lifting, repetitive movements, and poor ergonomics. Agricultural workers can use proper lifting techniques and ergonomic equipment to help prevent back pain.